The Relationship between Spiritual Well-Being and Resilience in Patients with Psoriasis - Mohammadhossein RahimZahedi; Camellia Torabizadeh; Majid Najafi Kalyani; Seyed Alireza Moayedi (Dermatology Research and Practice)
Psoriasis skin disease affects the patients’ health and quality of life to a great extent. Given the chronic nature of the disease, identifying the factors affecting adaptation to the disease can provide guidelines required for helping these patients deal with their problems. This study was conducted with the purpose of investigating the relationship between spiritual well-being and resilience in patients suffering from psoriasis. The present study is a descriptive-analytical work conducted in the largest city in the south of Iran in 2019. 150 patients diagnosed with psoriasis completed Ellison and Paloutzian’s Spiritual Well-Being Scale and Connor and Davidson’s Resiliency Scale. Data were analyzed using SPSS v. 20, descriptive (frequency distribution, mean, and standard deviation) and inferential statistics (Pearson, regression, and t-test). The significance level was set at 0.05. The obtained mean scores were 54.84 ± 13.25 for resilience and 73.22 ± 11.13 for spiritual health. Spiritual health predicted 43% of the variance of resilience, and all resilience-related factors had a significant positive relationship with spiritual well-being-related factors (P>0.05). An analysis of the relationship between demographic variables on the one hand and resilience and spiritual well-being on the other indicated that an increase in the patients’ academic status, duration of the disease, and age correlated with an increase in their resilience and spiritual well-being. Also, male patients and married patients were found to possess higher levels of resilience and spiritual well-being. According to the findings of the present study, spiritual well-being correlates with resilience in patients with psoriasis. Considering the chronic nature of the disease, it is recommended that more attention be paid to promoting spiritual health in the care plans of these patients.